REPRESENTATION OF SYMBOLS IN CINEMA ART - Usmanova Khumora Akhmadjonovna (Scholar Express Journal, 2022)
This article discusses the fact that the art of national cinema is an important tool that has a strong impact on human consciousness and thinking, public life, as well as the inner world and spirituality of our people, especially our youth. Uzbek films also feature symbolic images.
Keywords: Cinema; art; director; symbol